2004
DOI: 10.1172/jci200420267
|View full text |Cite
|
Sign up to set email alerts
|

Defects in secretion, aggregation, and thrombus formation in platelets from mice lacking Akt2

Abstract: Prior studies have shown that PI3Ks play a necessary but incompletely defined role in platelet activation. One potential effector for PI3K is the serine/threonine kinase, Akt, whose contribution to platelet activation was explored here. Two isoforms of Akt were detected in mouse platelets, with expression of Akt2 being greater than Akt1. Deletion of the gene encoding Akt2 impaired platelet aggregation, fibrinogen binding, and granule secretion, especially in response to low concentrations of agonists that acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
227
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(249 citation statements)
references
References 39 publications
19
227
0
2
Order By: Relevance
“…Although high concentrations of NO donors inhibit platelet activation, endogenous NO production in platelets occurs only when platelets are stimulated with various platelet agonists. Furthermore, potential NOS3 activation signals suggested in other cell types, namely, calcium elevation and the phosphoinositide 3-kinase-Akt pathway (42), all play roles in stimulating platelet activation but not in inhibiting platelet activation (22,(43)(44)(45)(46). Thus, our data that NO in fact plays biphasic roles in platelet activation provide an explanation for this apparent contradiction.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although high concentrations of NO donors inhibit platelet activation, endogenous NO production in platelets occurs only when platelets are stimulated with various platelet agonists. Furthermore, potential NOS3 activation signals suggested in other cell types, namely, calcium elevation and the phosphoinositide 3-kinase-Akt pathway (42), all play roles in stimulating platelet activation but not in inhibiting platelet activation (22,(43)(44)(45)(46). Thus, our data that NO in fact plays biphasic roles in platelet activation provide an explanation for this apparent contradiction.…”
Section: Discussionmentioning
confidence: 66%
“…It is important to note that we have recently found that phosphoinositide 3-kinase, like NOS3, plays a critical role in aggregation-dependent platelet secretion and secretiondependent second wave platelet aggregation (22). Others have reported a stimulatory role for Akt in platelet secretion and aggregation (45,46). Also, calcium elevation is induced by platelet agonists and aggregationdependent integrin outside-in signaling (47).…”
Section: Discussionmentioning
confidence: 95%
“…In this respect, it is interesting to note that endothelial nitric oxide synthase can be activated in endothelial cells by Akt (50), a serine/threonine protein kinase that is a downstream effector of phosphatidylinositol 3-kinase. We and others have shown that phosphatidylinositol 3-kinase and Akt play important roles in platelet secretion and second wave platelet aggregation (12,51,52). Thus, it will be interesting to investigate further whether activation of cGMP/PKG is downstream from the phosphatidylinositol 3-kinase-Akt pathway during platelet activation.…”
Section: Discussionmentioning
confidence: 96%
“…These agonists produced single platelet loss at concentrations that were similar to those previously found to cause aggregation of mouse platelets in traditional assays. 15,16 To validate our observations, we used a separate and distinct platelet marker, CD42d (GPV) and observed near-identical platelet counts when we analyzed separately for each marker over a range of activation conditions (r 2 5 0.998 by linear regression analysis; see supplemental Figure 1 on the Blood Web site).We next went on to confirm if single platelet loss in stimulated whole blood is an active, inhibitable process. To do this, we preincubated blood with the powerful platelet inhibitor PGI 2 and found significant reductions in the single platelet depletion induced by maximal tested concentrations of all agonists: collagen, 87 6 4% of single platelet loss vs 47 6 10% with PGI 2 ; PAR4-amide, 79 6 5% vs 25 6 9%; and U46619, 89 6 2% vs 26 6 7% ( Figure 2D-F).…”
mentioning
confidence: 81%